An efficient Chlorella sp.-Cupriavidus necator microcosm for phenol degradation and its cooperation mechanism - Yi, Tao; Shan, Ying; Huang, Bo; Tang, Tao; Wei, Wei; Quinn, Nigel W.T. (The Science of the total environment, 2020)
A Chlorella sp.-Cupriavidus necator (C. necator) microcosm was artificially established for phenol degradation. The cooperation relationship between Chlorella sp. and C. necator was initially demonstrated, and then the effects of Chlorella sp./C. necator inoculation ratio, light intensity, temperature and pH on the performance of this microcosm were systematically evaluated and optimized. The optimal conditions for phenol degradation were as follows: a Chlorella sp./C. necator inoculation ratio of 1:1, a light intensity of 110 μmol m−2 s−1, a temperature in the range of 25–32 °C and a pH in the range of 5.5–7.5. Under optimal conditions, this microcosm could degrade phenol with a maximum concentration of 1200 mg L−1 within 60 h. It was found that only when the phenol concentration was reduced to the tolerance concentration of microalgae, that is, the last stage of phenol degradation, the cooperation effect could be generated, indicating that the tolerance of microalgae to phenol may be more important than its degradation performance. Comparative transcriptomic analysis was conducted to discuss the cooperation mechanism of this microcosm subject to high phenol concentrations. The up-regulation of genes involved in photosynthesis and carbon fixation of Chlorella sp. demonstrated the CO2 and O2 exchange between Chlorella sp. and C. necator and their cooperation relationship. This study suggests that this microcosm has great potential for the bioremediation of phenol contaminants. [Display omitted] •A Chlorella sp.-Cupriavidus necator microcosm was artificially established for phenol degradation.•The influence of operating conditions on the phenol degradation was systematically evaluated and optimized.•This microcosm could completely degrade 600–1200 mg L−1 of phenol within 60 h.•The CO2 and O2 exchange between Chlorella sp. and Cupriavidus necator was discussed with comparative transcriptomic analysis.